Computation of genus and braid index for renormalizable Lorenz links - Franco, Nuno (2011)
We present and analyse two new algorithms to compute some combinatorial in- variants, the genus and the braid index, of renormalizable Lorenz links. We im- plement them, evaluate their complexities and compare it with the classical ones, confirming a drastic reduction of complexity.